ROBUSTA COFFEE BEANS DECREASE OF INFLAMMATION IN DENTAL CARIES - I Dewa Ayu Ratna Dewanti; I Dewa Ayu Susilawati; Pujiana Endah; Roedy Budirahardjo (UPT Penerbitan Universitas Jember)
The coffee plant is one commodity that is developedin kabuapaten Jember. Coffee chemical constituents,such as flavonoids, xanthine, antioxidants, alkaloids,polyphenols may serve as anti-inflammatory,antibacterial, platelet aggregation. Polyphenolbioavailability of coffee has also been studied.1.2.3While Namboodiripad, K. Srividya (2009) provedtheir coffee inhibition zone against S. mutans. Theimmune response of dental caries among othersrelated to cytokines are expressed odontoblast layer,such as IL-1β, IL-1α and TNF-α.4.5 Thus it is said thatcoffee is thought to inhibit dental caries by means ofmodulating the immune response. This niaccordance with the Decree of the Minister of Statefor Research and Technology of the Republic ofIndonesia Number: 02 / M / Kp / II / 2000 onDevelopment and Engineering for NationalDevelopment (JAKSTRA 2000-2004) in the field ofdentistry which has two areas of research focusinclude health field for prevention and treatment ofdiseases and new materials related to ceramics,polymer composites, engineering materials(materials science and engineering), as well as newmaterial derived from ingredients that are natural.6One of the natural ingredients that are known toeveryone is coffee. Where coffee is one of theexcellent programs that can improve theperformance of Jember University's Strategic Plan.This type of coffee is widely known in Indonesiathere are three kinds, namely Arabica, Robusta andLiberika. In general, farmers grow robusta, becausein this type of coffee has more superior properties,so it is very fast growing. Even the coffee is thedominant species of coffee plantations in Indonesia.In addition, it contains prolifenol Robusta coffee,caffeine and chlorogenic acid, which is higher thanthe other coffee types. Currently, the production ofrobusta coffee production reached third copiesworldwide.7.8 Coffee brews are very widelyconsumed in the world due to their pleasant flavorand taste as well as for their stimulating effect onthe mental and physical activities. Several years ago,in California, a research conducted by TakayukiShibamoto, a professor of environmental toxicology,found that freshly brewed coffee contains potentantioxidants equal to the amount found in threeoranges. Antioxidants in general have been linked toa number of potential health benefits, includingprotection against heart disease and cancer,protection against liver and colon cancer, type 2diabetes, and Parkinson's disease..9 Coffee chemicalconstituents, such as flavonoids, xanthine,antioxidants, alkaloids, polyphenols may serve asanti-inflammatory, antibacterial, plateletaggregation.1.2.3 Roasted coffee also has antiadhesiveproperties which prevent adhesion of S.mutans and other harmful materials on the teethand whiten teeth.4 Previous research by a team ofother researchers of Excellence coffee beans for thetreatment of cancer of the oral cavity, an article onPotential immunomodulatory coffee beans to dentalcaries and the potential immunomodulatory Robustabeans to dental caries.10.11.12 In this study Robustabeans made in the form of pasta because pastaShape is the most popular because it can be easilyused and harden quickly.Capping pupa is one of the more conservativetreatments to prevent dental caries has been on thepulp or pulp exposure due to mechanical factors.Interest Capping pulp to maintain the vitality ofdental pulp. Pulp tissue is important in the formationof secondary dentine and reparative dentin inresponse to biological and pathological stimuli.Capping pulp is the application layer or theprotective material or materials for treatment overan open pulp, such as calcium hydroxide which willstimulate the formation of reparative dentin.13Capping pulp after the treatment, the healingprocess will occur in the pulp tissue covering theinflammatory response, collagen formation and theformation of new dentin. Inflammatory responseshould occur as a sign of the host defense. Acuteinflammation occurs a few minutes, hours or days,while chronic inflammation occurs after acuteinflammation. Inflammatory played by inflammatorycells such as PMN (polymorphonuclear,mononuclear cells (monocytes, macrophages,lymphocytes, mast cells, plasma cells). PMN are cellsleading that respond to injury and most frequentlyProceeding ICMHS 2016 ISBN 978-602-60569-3-1174seen in inflammation. These cells react in the earlystages of inflammation (acute) up to 28 hours,followed by macrophages, lymphocytes and plasmacells (chronic).14 Chronic inflammation is said to bethe beginning of the healing process. Although theresponse innate was important in inflammation, butan adaptive response also plays a role, becausecytokines were producted by T cells induceinflammation. To obtain optimal care, the necessaryunderstanding in depth about how the composition,antibacterial properties, biocompatibility, effect ondentin and pulp as well as the technique of using aresin adhesive as a material Capping pulp directly. Inhandling damage teeth, either by decay or trauma,maintain vital pulp tissue remains the mostimportant things to be done by a dentist because ofthe non-vital teeth, the teeth tend to be susceptibleto fracture. The development of the field ofconservation science teeth adapted to thedevelopment of basic science related andtechnological advances applied which is thedevelopment of science in the field of clinical(clinical science). Dental conservation therapy aimsto maintain its position of teeth as long as possible inorder to work longer. This objective can be achievedby treating the hard tissue or soft tissue of a tooth totooth structure back to normal, or at least close tonormal.15